The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/07294360.2017.1304362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of honours programme participation in higher education: a propensity score matching approach

Abstract: Honours programmes have become part of higher education systems around the globe, and an increasing number of students are enrolled in such programmes. So far, effects of these programmes are largely under-researched. Two gaps in previous research on the effects of such programmes were addressed: (1) most studies lack a comparable control group of students not enrolled in honours programmes and (2) few studies have longitudinally investigated effects of honours programmes on student characteristics other than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
0
16
1
4
Order By: Relevance
“…Through the so-called Sirius subsidy in 2008, the Dutch government invested €61 million euros to further expand and stimulate excellence programmes in various institutions. In general, excellence programmes in the Netherlands are set up to complement the regular education programmes (Kool et al 2017). Although traditionally higher education in the Netherlands is geared towards promoting inclusivity and equality, in the last two decades additional curricula and programmes were developed for excellent students who are eager to pursue opportunities to further broaden and deepen their learning beyond their regular education programmes (Wolfensberger, van Eijl, and Pilot 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the so-called Sirius subsidy in 2008, the Dutch government invested €61 million euros to further expand and stimulate excellence programmes in various institutions. In general, excellence programmes in the Netherlands are set up to complement the regular education programmes (Kool et al 2017). Although traditionally higher education in the Netherlands is geared towards promoting inclusivity and equality, in the last two decades additional curricula and programmes were developed for excellent students who are eager to pursue opportunities to further broaden and deepen their learning beyond their regular education programmes (Wolfensberger, van Eijl, and Pilot 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This eligibility requirement makes it difficult to find a suitable control group of students in regular programmes, which is essential to assess the added value of participation in excellence programmes. In one of the few articles examining the effects of excellence programmes in the Netherlands, Kool et al (2017) include measures of motivation, creativity, and ability to assess students' development. This study revealed that students' development halfway through the excellence programme does not differ compared to students in regular programmes.…”
Section: Introductionmentioning
confidence: 99%
“…En consecuencia, partiendo de esta premisa planteada, que la formación dual en la Universidad de Cuenca no consideró en su diseño la asignación aleatoria de sus estudiantes para el ingreso a la carrera, una de las soluciones para evaluar diferencias en los resultados de interés es tratar de simular la aleatoriedad en la asignación. En este sentido, Caliendo y Kopeinig (2008) y Kool et al (2017) mencionaron que los métodos de emparejamiento como el psm pretenden construir un grupo de comparación o control lo más similar posible en términos de unas características observables.…”
Section: Pp 173-205 Gustavo Geovanni Flores-sánchez / Hernán Pedro Vunclassified
“…Bui et al (2011) concluderen echter dat excellentieprogramma's ook andere resultaten hebben dan alleen behaalde studieresultaten. Deze conclusie wordt ondersteund door Kool et al (2017) en Ghanizadeh (2017) die constateren dat studenten zich ook ontwikkelen op andere gebieden, zoals het kritisch denkvermogen. Zowel cognitieve uitkomsten zoals kritisch denken en behaalde cijfers als non-cognitieve vaardigheden zoals creativiteit zijn belangrijke uitkomstmaten van het onderwijs (Renzulli, 2002).…”
Section: Effecten Van Excellentieprogramma'sunclassified